Effective Learning for Early Childhood during Global Pandemic - Mohammad Fauziddin; Diana Mayasari; Lussy Midani Rizki (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to examine the effectiveness of online learning based on interactive media with parental involvement on early childhood learning outcomes at TK Mutiara Bunda Bangkinang, group B, in 2021. The research method employed was an experimental design using a pretest-posttest control group design. The study involved 40 children, consisting of 20 in the experimental group and 20 in the control group. Research instruments included a learning achievement test and a parental involvement questionnaire. The findings revealed a significant improvement in the learning outcomes of the experimental group compared to the control group. The average pretest score of the experimental group was 52.4, which increased to 80.5 in the posttest, while the control group improved from 53.1 to 68.2. Aspect-based analysis indicated significant improvements in cognitive skills, fine motor skills, and parental involvement in the experimental group. An independent t-test showed a p-value of 0.002 ( 0.05) and an effect size of 0.94, categorized as large. Thus, it can be concluded that online learning based on interactive media with parental involvement is effective in enhancing early childhood learning outcomes and encouraging active parental engagement in the learning process.